2005
DOI: 10.1111/j.0105-1873.2005.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal water loss and incidence of hand dermatitis in a prospectively followed cohort of apprentice nurses

Abstract: The purpose of the study was to evaluate the incidence of hand dermatitis, the impact of potential risk factors and the efficacy of skin bioengineering in a prospectively followed cohort of apprentice nurses. 104 participants were prospectively followed for 3 years. Before the start of training, after about 1 year and in the third year of occupational exposure, a standardized questionnaire was distributed, and a clinical examination with skin bioengineering of the dorsum of hand and forearm was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 20 publications
6
47
0
2
Order By: Relevance
“…Only minor differences in TEWL values were observed within the same treatment and no statistically significant difference between Propyless® lotion and Fenuril® cream was observed while an improvement of other skin parameters such as itching and irritation was observed. Earlier studies showed a good correlation between TEWL in psoriatic skin lesions and the severity of psoriasis (11) while TEWL has not been confirmed to be a good measure of risk for hand dermatitis (12).…”
Section: Discussionmentioning
confidence: 95%
“…Only minor differences in TEWL values were observed within the same treatment and no statistically significant difference between Propyless® lotion and Fenuril® cream was observed while an improvement of other skin parameters such as itching and irritation was observed. Earlier studies showed a good correlation between TEWL in psoriatic skin lesions and the severity of psoriasis (11) while TEWL has not been confirmed to be a good measure of risk for hand dermatitis (12).…”
Section: Discussionmentioning
confidence: 95%
“…Contact dermatitis (CD) is one of the most common occupational diseases in industrialized countries. In European surveys among workers and apprentices in ‘high‐risk’ occupations, such as hairdressing, health care and metalworking, the 1‐year prevalence varied between 20% and 30%, and mild skin symptoms were present in up to 50% of the workers or apprentices 1–7 . CD is commonly divided into allergic CD (ACD) and irritant CD (ICD), of which ICD is the more common in occupational settings 8 .…”
mentioning
confidence: 99%
“…There have also been attempts to use biomarkers such as transepidermal water loss [17]. The observations of the nurses themselves remain important however.…”
Section: The Prevalence Of Hand Dermatitis In Nurses: a Narrative Revmentioning
confidence: 99%